Avaliação da viabilidade técnico-econômica e térmica de um sistema de cogeração a biogás com base em dados experimentais em escala laboratorial - Campani, Gabriel Pavan (Universidade Federal de São Carlos, 2025)
This work evaluated the technical, energetic, and economic feasibility of a pilot-scale biogas cogeneration system at the Federal University of São Carlos (UFSCar), using food waste from the University Restaurant and pruning residues generated on campus. Based on characterization data and bench-scale mono and co-digestion assays, institutional scale biogas flows were estimated, the performance of an Otto-cycle engine-generator was modeled, and a pilot biodigester was sized according to substrate availability. The scenarios analyzed exhibited distinct behaviors. Mono-digestion showed higher energy potential, producing approximately 3.46 kWh per month of electricity and 4.58 kWh per month of heat, whereas co-digestion resulted in about 2.94 kWh per month of electrical energy and 3.89 kWh per month of thermal energy. The estimated continuous nominal capacities were 5.34 kW for mono-digestion and 4.54 kW for co-digestion, with digester volumes of 44 m³ and 83 m³, respectively. A global efficiency of 79 percent reinforced the suitability of cogeneration for small-scale applications, particularly for meeting the thermal demands of the University Restaurant. Intermittent operation scenarios were also evaluated, yielding higher nominal power outputs but incurring greater costs and impractical payback times, thus being considered unsuitable for implementation. The economic analysis highlighted the decisive role of heat recovery, providing annual savings of 58,080.20 BRL for mono-digestion and 62,007.21 BRL for co-digestion. Payback times were betweeb 4 and 25 years, according with the CAPEX oscilation, indicating greater feasibility for continuous co-digestion. It is concluded that biogas cogeneration at UFSCar is technically viable and economically promising when operated continuously with co-digestion, contributing to waste valorization, cost reduction, and the strengthening of institutional sustainability initiatives.
Evaluation of the technical-economic and thermal feasibility of a biogas cogeneration system based on laboratory-scale experimental data
Keywords: cogeração; biogás; resíduos alimentares; análise econômica; ENGENHARIAS::ENGENHARIA MECANICA::ENGENHARIA TERMICA::APROVEITAMENTO DA ENERGIA; 7. Energia limpa e acessível; 9. Indústria, Inovação e Infraestrutura; 11. Cidades e Comunidades Sustentáveis; 12. Consumo e Produção Responsáveis; 13. Ação contra a Mudança Global do Clima; 4. Educação de Qualidade